IMPLEMENTASI PEMBELAJARAN IPS GEOGRAFI BERBASIS KONTEKSTUAL DI MADRASAH - Akbar, Rofiq Faudy (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
This study aims to determine; (1) Can the implementation of contextual-based learning methods in class X social science subjects improve student motivation? (2) Does the implementation of contextual-based learning methods in class X social science geography subjects improve student achievement? (3) What is the response of class X students regarding the application of contextual based learning methods to geography social studies subjects ? The method used in this study is quantitative with an analytical descriptive approach. The results of this study indicate that from the data on the recapitulation of students' activeness in the discussion, CTL is able to increase motivation shown by the activity of students in the discussion, it can be seen from the number of students who are quite active from the first cycle to the second cycle. Learning achievement of students from the first cycle to the second cycle has increased, and classically with the application of contextual learning methods / CTL (contextual teaching learning) fulfills an increase in competency standards. Recapitulation of observational data about contextual learning generally shows that students' responses increase, all in the categories tend to agree and agree.Keywords:IPS Geography, Contextual, Madrasah